A FORENSIC LINGUISTIC APPROACH TO INTERPRETING A HATE SPEECH CASE ON SOCIAL MEDIA - Yulia Sari Harahap; Nurhafni Siregar (UIN Sumatera Utara, 2022)
Hate speech is defined as speech that involves hate and is meant to have specific consequences, either directly or indirectly. Hate speech is becoming more common as the internet era progresses. Hate speech can be delivered individually or in groups, resulting in heated debates and difficulties in the community. This study aims to explain the types of hate speech on Tiara marlen on social media. The method use in this research is descriptive qualitative method, data collection techniques in the form of viewing and documentation. The method used in supporting this research is utterances, to determine whether the comments are included in to positive or negative categories.In this study used were 15 coments as research object.